Mostly one shade of green: Sierra magazine and the discursive exploitation of "authentic nature" - Walker, Brittany A., author; Champ, Joseph, advisor; Kodrich, Kris, committee member; Cross, Jennifer, committee member (Colorado State University. Libraries, 2017)
Environmental discourse from the mainstream environmental movement often relies on nature-based schema and a human-nature dichotomy in describing the environment, which can prioritize natural spaces over human-occupied spaces. It can also run counter to the aims of the environmental justice movement to protect vulnerable humans from harm. The goal of this research was to better understand how the largest environmental organization in the U.S. conceptualizes nature and the environment, and how these conceptualizations may be informing the priorities of the Sierra Club and the environmental movement more broadly. The research question of this study was: How does the Sierra Club, in the discourse represented by its magazine, present a nature-based schema and a human-nature dichotomy which indicates a preference for the idea of nature protection at the expense of protection for the human sphere? This study aimed to answer this question by performing a critical discourse analysis of six issues of Sierra magazine from 2011-2016, a publication popular with, and influential to, environmentalists. Findings indicate that Sierra magazine reveres authentic nature more greatly than other spaces and that authentic nature is exploited for profit. Authentic nature experiences are also discursively reserved for the elite, rather being presented inclusively. Sierra heavily emphasizes nature protection and the enjoyment of nature, while alternative perspectives are rarely featured and make Sierra's focus on authentic nature stand out even more.